The challenge of reconciling development objectives in the context of demographic change - John Provo; Mel Jones (Revue de Géographie Alpine)
This paper considers whether the US Appalachian Regional Commission (ARC) Asset-Based Development Initiative (ABDI) reconciles economic development objectives in communities experiencing demographic change. Through a case study approach utilizing key informant interviews in Southwest Virginia communities and a review of ARC-funded projects, the authors consider two main questions. Did community leadership change or adapt to the program? Were new projects demonstrably different in objectives, content, or outcomes than past projects? Economic and demographic similarities between Alpine and Appalachian communities, particularly in the role of in-migrants, suggest that this study’s findings will be relevant for other mountain regions and could contribute to a conversation among international scholars of mountain development.